1990
DOI: 10.1046/j.1420-9101.1990.3050329.x
|View full text |Cite
|
Sign up to set email alerts
|

An integrative analysis of phylogenetic relationships among newts of the genus Triturus (family Salamandridae), using comparative biochemistry, cytogenetics and reproductive interactions

Abstract: All the currently available data with regard to morphology, palaeontology, biochemical genetics, reproductive interactions and behaviour have been collated and analysed with combinations of phenetic and numerical phylogenetic methods, and integrated into a consensus evolutionary tree for European newts of the genus Triturus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
2

Year Published

1993
1993
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 65 publications
(20 reference statements)
2
87
2
Order By: Relevance
“…Monophyly of Neurergus is strongly supported (Steinfartz et al, 2002), but its placement as the sister group to a lineage of Triturus vittatus contributes to the nonmonophyly of Triturus. Molecular phylogenetics of Triturus has received considerable attention (Busack et al, 1988;Giacomo and Balletto, 1988;Halliday and Arano, 1991;Macgregor et al, 1990;Zajc and Arntzen, 1999) with some molecular studies indicating that it is not monophyletic (Titus and Larson, 1995;Zajc and Arntzen, 1999). Furthermore, molecular (mtDNA and nuclear rDNA) phylogenetic investigations have found that Calotriton likewise renders Triturus nonmonophyletic (Caccone et al, 1994(Caccone et al, , 1997Carranza and Amat, 2005).…”
Section: Phylogenetics Of Calotriton Euproctus Neurergus and Triturusmentioning
confidence: 99%
See 1 more Smart Citation
“…Monophyly of Neurergus is strongly supported (Steinfartz et al, 2002), but its placement as the sister group to a lineage of Triturus vittatus contributes to the nonmonophyly of Triturus. Molecular phylogenetics of Triturus has received considerable attention (Busack et al, 1988;Giacomo and Balletto, 1988;Halliday and Arano, 1991;Macgregor et al, 1990;Zajc and Arntzen, 1999) with some molecular studies indicating that it is not monophyletic (Titus and Larson, 1995;Zajc and Arntzen, 1999). Furthermore, molecular (mtDNA and nuclear rDNA) phylogenetic investigations have found that Calotriton likewise renders Triturus nonmonophyletic (Caccone et al, 1994(Caccone et al, , 1997Carranza and Amat, 2005).…”
Section: Phylogenetics Of Calotriton Euproctus Neurergus and Triturusmentioning
confidence: 99%
“…Caccone et al, 1997;Carranza and Amat, 2005;Chan et al, 2001;Lu et al, 2004;Steinfartz et al, 2000Steinfartz et al, , 2002Weisrock et al, 2001), yet many species-level relationships require further resolution. Evolution of the genus Triturus has been studied extensively (Halliday and Arano, 1991), yet phylogenetic resolution among species remains ambiguous, even with a host of morphological, molecular, and behavioral data (Giacomo and Balletto, 1988;Macgregor et al, 1990;RaWnski and Arntzen, 1987;Zajc and Arntzen, 1999). Monophyly of the genus Triturus was rejected by the mtDNA studies of Titus and Larson (1995), based on two species.…”
Section: Introductionmentioning
confidence: 99%
“…In such measurements the peaks in histograms became wider, the CV were increased, but the positions of peaks of experimental and standard samples remained as they were in the case of non-fixed cells. It is interesting that in (42) the authors fixed the nuclei of salamandrids and the control species (Xenopus Zaeuis) in ethanol before making their measurements.…”
Section: Measurement Peculiaritiesmentioning
confidence: 99%
“…Flow cytometry is one of the most sensitive techniques used for quantifying cellular DNA (reviews in 14, 52,62) and has been used to determine the nuclear DNA content of many animal species, including vertebrates from fishes to mammals (11,12,36,37,40,42,53,57,58,60), and mollusks (1,191. It was also used for determination of cell or sperm ploidy in fishes, amphibians, and reptiles (1,2,6,7,21,22, 35,61), sex identification in birds (45), as well as for investigation of genome elimination of one of the parents in hybridogenetic frogs (10,661 and hybrid fishes (27).…”
mentioning
confidence: 99%
“…Hybrids of intermediate phenotype were recorded in Ukraine by Hofmann (1908), Kushniruk (1963) and Bannikov (1969), in Romania by Fuhn (1963) and Fuhn et al (1975), in Poland by SzeligaMierzeyewski & Ulasiewicz (1931), Juszczyk &Świerad (1984, Rafiński (1985Rafiński ( , 1988, Pecio & Rafiński (1985), Rafiński & Pecio (1989) and Babik et al (2003), and in the Czech Republic described by Rehák (1992Rehák ( , 1993, Zwach (1992), Šálek (1993), Kotlík et al (1997), Kotlík & Zavadil (1999) and Zavadil et al (2003Zavadil et al ( , 2004. Besides hybrids in nature, hybrids in captivity were obtained during laboratory experimental crosses (Wolterstorff 1925;Geyer 1953Geyer , 1954Macgregor et al 1990;Cogȃlniceanu 1992Cogȃlniceanu , 1994Michalak & Rafiński 1999). A detailed survey of T. vulgaris and T. montandoni hybrid zone in Poland exhibits its mosaic pattern, i.e., genetic composition of populations is only weakly associated with their geographic position (Babik et al 2003).…”
Section: Introductionmentioning
confidence: 99%